Implementasi Metode Weighted Product dan SMART Dalam Menentukan Lokasi Usaha Strategis Bagi Pelaku UMKM - Agung Triayudi; Muhammad Faizal; Rima Tamara Aldisa (Journal of Information System Research (JOSH), 2023)
In the business world, choosing the right business location is one of the main things that must be considered, the problem that occurs is choosing a business location that is not right for the business actors themselves. Therefore, an application is needed that helps business actors to determine the location. strategic for the business they are involved in. In this research, a decision support system application was made to make it easier for business actors to determine the location according to the criteria. Decision support applications are considered effective enough to create a ranking in determining strategic locations for business actors. The Weighted Product and SMART methods using 7 alternative data shows that the two methods produce data that is accurate and suitable when applied as a ranking for selecting business locations. The 2 methods have an elective execution score and the results of the weight values applied to each technique.